5′-terminal glycosylation of protein-coding transcripts: An epitranscriptomic modification that prolongs mRNA lifetimes - Tithi Banerjee; Daniel J. Luciano; Joel G. Belasco (Proceedings of the National Academy of Sciences, 2025)
Glycosylation is among the most common molecular modifications in living organisms, one that affects the function of myriad macromolecules: mostly proteins, lipids, and polysaccharides of various kinds but also a few specific noncoding RNAs that undergo glycosylation at an internal site. Here we expand the glycome by showing that protein-coding transcripts can also be glycosylated, but in the form of a 5′-terminal glucose cap. These caps are present on up to 30 to 40% of the 5′ ends of U-initiated mRNAs in Escherichia coli , a remarkably high level of noncanonical capping that requires no transcript or promoter characteristic other than a 5′-terminal U. By contrast, no N -acetylglucosamine caps are evident. Due to their resistance to enzymatic removal, glucose caps can greatly prolong the cellular lifetime of mRNA by impeding its degradation via a 5′-end-dependent mechanism. The prevalence and protective impact of glucose caps set them apart from other bacterial RNA caps. This epitranscriptomic modification has the potential to selectively increase the synthesis of bacterial proteins encoded by U-initiated transcripts, especially after transcription is downregulated.